MIGA Annual Report 2018 - Multilateral Investment Guarantee Agency (Multilateral Investment Guarantee Agency, Washington, DC, 2018)
MIGA provides political risk insurance and credit enhancement for cross-border private sector investors and lenders, in support of projects in developing member economies across the world. Marking its 30th year of operation, the Multilateral Investment Guarantee Agency (MIGA) has become the third leading institution among the MDBs in terms of mobilizing direct private capital to low- and middle-income countries. This year, MIGA issued a record $5.3 billion in political risk insurance and credit enhancement guarantees, helping finance $17.9 billion worth of projects in developing countries. New issuances and gross outstanding exposure—at $21.2 billion this year—almost doubled as compared to fiscal 2013.